Exploring the impact of ambient annealing on the superconducting properties of Y-123 with marine waste-derived chitosan additives - Yap, Siew Hong; Awang Kechik, Mohd Mustafa; Mohamed, Arebat Ryad Alhadei; Khoerunnisa, Fitri; Baqiah, Hussien; Chen, Soo Kien; Lim, Kean Pah; Shabdin, Muhammad Kashfi; Humaidi, Syahrul; Mohd Zaid, Mohd Hafiz; Yaakob, Yazid; Abdul Karim, Mohd Khalis; et al. (Elsevier, 2025)
The investigation focused on evaluating the influence of ambient annealing on the superconducting performance of the YBa2Cu3O7-δ (Y-123) system. In this context, chitosan (CTS), a natural fine nucleating agent derived from marine waste, was incorporated to examine its effect on both superconducting properties and excess conductivity. Using the thermal treatment method, the Y-123 matrix was incorporated with various concentrations of CTS deficiency ranging from 0.0100 wt% to 0.6000 wt%. The phase analysis confirmed the formation of the orthorhombic crystal structure characteristic of the primary Y-123 phase, accompanied by secondary non-superconducting phases including BaCuO2 and Y-211. The crystal structure exhibits a high degree of orthorhombicity (0.0008) and an enhanced oxygen content (O7-δ = 6.82). Under microstructural analysis, the grain degradation-recrystallization and the formation of superconducting nano-entities along spiral grain growth were found on the surface morphology. A notable improvement in both intergranular and intragranular properties was observed, along with stable oxygen content and grain size, as evidenced by the DC resistivity measurements. Additionally, all added CTS specimens showed substantial improvements in critical temperatures and superconducting width transition temperatures. The Jc(0) exhibited a threefold enhancement in Y-123-CTS as compared to pure Y-123, reaching a peak value of 10.30 × 106 A/m2 for the Y-123 added with 0.0375 wt% CTS. This research emphasizes a sustainable strategy involving the integration of the natural polymer chitosan (CTS) into Y-123 superconducting specimens synthesized exclusively via a thermal treatment process under ambient conditions. The approach aims to optimize superconducting performance while adhering to the objectives of worldwide Sustainable Development Goals, specifically those advocating for affordable and clean energy as well as the development of sustainable cities and communities.